Огляд архітектури Versal ACAP - Скорбатюк, М. В.; Свид, І. В. (ХНУРЕ, 2023)
Xilinx Versal ACAP is a powerful, adaptive platform that can be used for high-performance and adaptive computing solutions in the cloud, edge and smart device industries. In particular, Versal ACAP has found implementation in the following industries: 5G, data centers, smart factories; auxiliary electronic control system of the car and parking, machine learning, etc.
Keywords: Xilinx; ACAP; Versal; архітектура; AMD